Collapse simulation of reinforced concrete frame structures. (4th December 2015) - Feng, Decheng; Kolay, Chinmoy; Ricles, James M.; Li, Jie
Summary: Study of collapse‐resisting properties of structures has attracted widespread attention because of frequently occurring earthquakes and extreme events (e.g. blast) around the world. The developments in computational methods have enabled researchers to numerically simulate the collapse of structures under different kinds of loadings and provide reliable assessments of the collapse performance of structures. The dynamic nature of structural collapse requires a direct integration algorithm to solve the equations of motion of the numerical simulation model. A major concern in such simulations is the computational efficiency, which stems from the need to use a small time step size in both implicit algorithm and explicit algorithm. In this paper, modeling techniques to simulate typical failure mechanisms in reinforced concrete frame structures combined with the application of the recently developed explicit, unconditionally stable, parametrically dissipative KR‐α integration method to investigate collapse simulation are presented. A fiber beam‐column element is used to model the frame members, where the material nonlinearities, especially material softening, are simulated by a plastic damage model combined with a failure criterion. Numerical examples are presented to illustrate the proposed collapse simulation technique. The results indicate that the proposed technique provides an accurate result and has exceptional computational efficiency. Copyright © 2015 John Wiley & Sons, Ltd.